USE OF E-LEARNING MODELS FOR LESSON ACTIVITIES ON MICROCONTROLLER'S EYES TO IMPROVE STUDENT LEARNING OUTCOMES IN VOCATIONAL EDUCATION IN ELECTRICAL ENGINEERING SULTAN AGENG TIRTAYASA UNIVERSITY - Irwanto Irwanto (Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study is to determine whether the use of E-learning with lesson activities can improve the learning outcomes of vocational education students in electrical engineering. Especially the class of 2017 who took microcontroller courses in odd semester 2019/2020 academic year. When compared with conventional learning used in learning. The research method used in this study is a quantitative research method with a quasi experimental approach. In the study conducted by providing treatment of the relevant research subjects using the pretest-posttest control group design experimental design. The results of the study found that the increase in learning outcomes with E-learning learning media with lesson activities was higher than the normalized gain index value of 0.36 when compared with student learning outcomes with conventional learning with the normalized gain index of 0.26. In increasing the learning outcomes of PVTE students by utilizing E-learning learning media lesson activities are better than increasing student learning outcomes by utilizing conventional learning media. T-Test Test Results prove that student learning outcomes using E-learning are better than student learning outcomes that apply conventional learning.